Sport and exercise medicine/physiotherapy publishing has a gender/sex equity problem: we need action now!. (11th January 2023) - Cowan, Sallie M; Kemp, Joanne L; Ardern, Clare L; Thornton, Jane S; Rio, Ebonie Kendra; Bruder, Andrea M; Mosler, Andrea Britt; Patterson, Brooke; Haberfield, Melissa; Roughead, Eliza A; Hart, Harvi; To, Laura; et al.
Abstract : Objectives: We aimed to determine (1) the proportion of women authors overall, in first (lead) and last (senior) author positions, (2) the proportion of women research participants and (3) the association between women in first and/or last author positions and the proportion of women research participants in original research articles and editorials/opinion pieces in four sport and exercise medicine/physiotherapy journals. Methods: The journals evaluated were the British Journal of Sports Medicine, Journal of Orthopaedic and Sports Physical Therapy, Physical Therapy in Sport and International Journal of Sports Physical Therapy . We reviewed all original research articles and editorials/opinion pieces published in 2008, 2009, 2018 and 2019. For each, we aimed to determine the gender/sex of all authors (through gender pronouns, Google Scholar, ResearchGate, institutional profiles, personal websites, photographs and/or social media), and the gender/sex of study participants reported as 'female' or 'male' or 'women' or 'men' or 'girls' or 'boys'. Results: We included 952 original studies and 219 editorials/opinion pieces. There were 5146 authors of original studies and 706 authors of editorials/opinion pieces. Compared with 2008/2009, the proportion of women as first and last authors was 3.6% (33.0% compared with 29.4%) and 4.8% (33.2% compared with 27.4%) higher respectively in 2018/2019. On average, the proportion of women participants in original studies remained largely unchanged over the 10-year period, only 10% of all participants were women in studies. Conclusion: Women are strikingly under-represented in first and last author positions, as are women participants in sports and exercise medicine/physiotherapy journals.